Plasma Soluble CD146 as a Potential Diagnostic Marker of Acute Rejection in Kidney Transplantation - Liao, Jun; Fu, Qian; Chen, Wenfang; Li, Jun; Zhang, Wenhui; Zhang, Huanxi; Gao, Yifang; Yang, Shicong; Xu, Bowen; Huang, Huiting; Wang, Jiali; Li, Xirui; et al. (Frontiers in Medicine, 2020)
Previous studies have implicated the role of CD146 and its soluble form (sCD146) in the pathogenesis of inflammatory diseases. However, the association between CD146 and acute rejection in kidney transplant patients remains unexplored. In this study, fifty-six patients with biopsy-proved rejection or non-rejection and 11 stable allograft function patients were retrospectively analyzed. Soluble CD146 in plasma was detected in peripheral blood by enzyme linked immunosorbent assay (ELISA), and local CD146 expression in graft biopsy was detected by immunohistochemistry. We found that plasma soluble CD146 in acute rejection recipients was significantly higher than in stable patients without rejection, and the biopsy CD146 staining in the rejection group was higher than that of the non-rejection group. Multivariate analysis demonstrated soluble CD146 as an independent risk factor of acute rejection. The area under the receiver operating characteristic curve (AUC) of sCD146 for AR diagnosis was 0.895, and the optimal cut-off value was 75.64 ng/ml, with a sensitivity of 87.8% and a specificity of 80.8%, which was better than eGFR alone (P = 0.02496). Immunohistochemistry showed CD146 expression in glomeruli was positively correlated with the Banff-g score, and its expression in tubules also had a positive relationship with the Banff-t score. Therefore, soluble CD146 may be a potential biomarker of acute rejection. Increased CD146 expression in the endothelial or tubular epithelial cells may imply that endothelial/epithelial dysfunction is involved in the pathogenesis of immune injury.